Investment, Savings, and Spending Habits of Indian Digital Natives/Millennials: A Comparative Study of Age Group Cohorts - Narayanaswamy, T.; Shubha, A.; Gokilavani, R.; Ajay, N. P. (Indian Journal of Research in Capital Markets, 2022)
This research work attempted to study and compare the investment pattern, spending level, and saving habits of three age cohorts, namely pre-millennials (born before the 1980s), millennials (born between 1981 & 1996), and post-millennials (born after 1996) in India. Secondary data from the surveys conducted by YouGov, Mint News, and the Centre for Policy Research (CPR) during the years 2019 and 2020 were used in the study. Major statistical tools used for the study were descriptive statistics, ranking, and chi-square analysis. The demographic study results showed that the money saved by these cohorts varied according to their income levels, and income influenced saving habits more than the age factor. In terms of investment, more proportion of the money was saved in deposit/savings schemes rather than market-related investments. While considering the spending pattern, purchasing vehicles, houses, travel, future needs and priorities, income levels, and financial security were found to play a major role. Post-millennials and millennials preferred savings and investment by purchasing fixed assets and paying for education; whereas pre-millennials saved for retirement, contingencies, and children’s education.